KEDUDUKAN DAN KEKUATAN HUKUM SURAT KEPUTUSAN BERSAMA MENTERI PENDIDIKAN DAN KEBUDAYAAN, MENTERI DALAM NEGERI DAN MENTERI AGAMA (SKB TIGA MENTERI) TENTANG PENGGUNAAN PAKAIAN SERAGAM DAN ATRIBUT DITINJAU DARI UU NOMOR 12 TAHUN 2011 - Fitri Angelia H Sinambela; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The formation of laws and regulations is a form of government effort in setting orders or prohibitions that aim to regulate and protect their citizens. The laws and regulations that are created will be divided into levels or hierarchies. In the hierarchy of legislation, the presence of a new regulation must be relevant to the existing regulations. This is expected to reduce the arbitrariness of the regulations, so that there are no violations of the law. The laws and regulations that are made have the basis of formation which is regulated by the constitution. It becomes a problem if the process of forming laws and regulations does not go through procedures that result in uncertainty about the position and legal force of the laws and regulations. One of the products of legislation whose position is questioned is the Joint Decree. In the application of the law, the Joint Decree contains substance which contains matters related to law enforcement and application. This Joint Decree is categorized as a policy issued by two or more Ministers, which aims to solve urgent problems in Indonesian society. A Joint Decree in this case is issued by the Minister of Education and Culture, the Minister of Religion and the Minister of Home Affairs regarding the use of uniforms and attributes. Joint Decree which aims to protect the freedom of citizens to choose and practice their religion without the obligation to use uniforms and attributes with certain religious nuances. However, the position and legal force of the Joint Decree are not yet clear, making this statutory regulation unable to be applied optimally. So the authors set several objectives of this research.The aims of this research are: First, to know and understand the position of the Joint Decree regarding the use of uniforms and attributes. Second, to understand the legal force of the Joint Decree after the issuance of the Supreme Court decision. And third, to find out the construction of the concept of proper legal regulation on the use of clothes and attributes. The type of research carried out is normative legal research or library law research using research methods on legal principles.From the results of the study, three main things can be concluded. First, the Joint Decree is a policy, not a regulation. Second, the Joint Decree cannot be tested at the Supreme Court, and Third, it is necessary to establish new laws and regulations, in order to continue to carry out the role of the state as a tool to protect its citizens.Keywords: Position – Joint Decree – Protection of Rights